In vitro analyses of Artemisia extracts on Plasmodium falciparum suggest a complex antimalarial effect. - Brian M Gruessner; Pamela J Weathers (PLoS ONE, 2021)
Dried-leaf Artemisia annua L. (DLA) antimalarial therapy was shown effective in prior animal and human studies, but little is known about its mechanism of action. Here IC50s and ring-stage assays (RSAs) were used to compare extracts of A. annua (DLAe) to artemisinin (ART) and its derivatives in their ability to inhibit and kill Plasmodium falciparum strains 3D7, MRA1252, MRA1240, Cam3.11 and Cam3.11rev in vitro. Strains were sorbitol and Percoll synchronized to enrich for ring-stage parasites that were treated with hot water, methanol and dichloromethane extracts of DLA, artemisinin, CoArtem™, and dihydroartemisinin. Extracts of A. afra SEN were also tested. There was a correlation between ART concentration and inhibition of parasite growth. Although at 6 hr drug incubation, the RSAs for Cam3.11rev showed DLA and ART were less effective than high dose CoArtem™, 8 and 24 hr incubations yielded equivalent antiparasitic results. For Cam3.11, drug incubation time had no effect. DLAe was more effective on resistant MRA-1240 than on the sensitive MRA-1252 strain. Because results were not as robust as observed in animal and human studies, a host interaction was suspected, so sera collected from adult and pediatric Kenyan malaria patients was used in RSA inhibition experiments and compared to sera from adults naïve to the disease. The sera from both age groups of malaria patients inhibited parasite growth ≥ 70% after treatment with DLAe and compared to malaria naïve subjects suggesting some host interaction with DLA. The discrepancy between these data and in-vivo reports suggested that DLA's effects require an interaction with the host to unlock their potential as an antimalarial therapy. Although we showed there are serum-based host effects that can kill up to 95% of parasites in vitro, it remains unclear how or if they play a role in vivo. These results further our understanding of how DLAe works against the malaria parasite in vitro.